2016
DOI: 10.1136/bjophthalmol-2015-307945
|View full text |Cite
|
Sign up to set email alerts
|

Bruch's membrane opening changes and lamina cribrosa displacement in non-arteritic anterior ischaemic optic neuropathy

Abstract: At onset, a significant PT thickening, backward LC movement and BMO enlargement occurred in NAION eyes compared with unaffected eyes, and these changes significantly reversed during follow-up. PTT and RNFL changes were significantly correlated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…However, they did not include normal controls and did not measure BMO area. 13 In this study, we also found that the prelaminar tissue thickness decreased in NAION eyes compared to unaffected fellow eyes. Similarly, Henkind et al 22 demonstrated the atrophy of the prelaminar tissue in the histological findings of a 67-year-old woman with arterial anterior ischemic optic neuropathy.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, they did not include normal controls and did not measure BMO area. 13 In this study, we also found that the prelaminar tissue thickness decreased in NAION eyes compared to unaffected fellow eyes. Similarly, Henkind et al 22 demonstrated the atrophy of the prelaminar tissue in the histological findings of a 67-year-old woman with arterial anterior ischemic optic neuropathy.…”
Section: Discussionsupporting
confidence: 70%
“…12 A recent study has reported prelaminar tissue thickening and BMO enlargement in the acute edematous NAION eyes compared with unaffected eyes, with reversal of changes during follow-up. 13 The morphologic characteristics of the optic disc before the onset of NAION could provide further information regarding the possible underlying predisposing factors through investigating the unaffected fellow eyes compared to control healthy eyes. Therefore, we measured the peripapillary retinal nerve fiber layer (pRNFL) and ONH quantitative parameters, including the anterior LC depth, prelaminar tissue thickness, BMO distance, and BMO area in patients with chronic unilateral NAION, their unaffected fellow eyes, and healthy normal subjects using the Spectralis-OCT software and compared the results among these groups.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, BMO expansion has been demonstrated immediately after intravitreal aflibercept injection 24 and in NAION eyes at onset that reversed with the follow-up. 36 ONH deformation by means of an IOP increase or optic nerve swelling can be explained by two mechanisms or forces; one pushing LC backwards and compressing the PT and other related to the hoop stress (inner circumferential pressure supported by the peripapillary sclera) which results in the sclera and BMO expansion. 7 Apart from the BMO enlargement during acute NAION, Rebolleda et al 36 observed a significant posterior LC displacement that returned to normal in the atrophic stage, with no significant differences in LCD with the fellow unaffected eye.…”
Section: Discussionmentioning
confidence: 99%
“…36 ONH deformation by means of an IOP increase or optic nerve swelling can be explained by two mechanisms or forces; one pushing LC backwards and compressing the PT and other related to the hoop stress (inner circumferential pressure supported by the peripapillary sclera) which results in the sclera and BMO expansion. 7 Apart from the BMO enlargement during acute NAION, Rebolleda et al 36 observed a significant posterior LC displacement that returned to normal in the atrophic stage, with no significant differences in LCD with the fellow unaffected eye. The above-mentioned mechanisms are present in both POAG and NAION eyes, but changes seem to be permanent just in glaucoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although BMO widening also has been reported in nonarteritic anterior ischemic optic neuropathy, the underlying mechanisms are completely different, and this is the first time that BMO expansion was reported after intravitreal injection. 30 Average prelaminar tissue thinned by 6% 5 minutes after injection, returning to baseline thickness 30 minutes later. Cupping enlargement and prelaminar tissue compression also have been described during an artificial increment of IOP in nonglaucomatous eyes using an ophthalmodynamometer.…”
Section: Discussionmentioning
confidence: 96%